A promoter effect on hydrodeoxygenation reactions of oleic acid by zeolite beta catalysts - I. Nur Azreena; H.L.N. Lau; N. Asikin-Mijan; M.A. Hassan; Saiman Mohd Izham; E. Kennedy; M. Stockenhuber; M.S. Mastuli; Fahad A. Alharthi; Abdulaziz Ali Alghamdi; Yap, Taufiq Yun Hin (Elsevier, 2021)
In this study, various metal-modified zeolite beta-based catalysts such as La(10)zeo(90), Co(10)zeo(90), Fe(10)zeo(90), Mg(10)zeo(90), Mn(10)zeo(90) and Zn(10)zeo(90) were investigated in the hydrodeoxygenation (HDO) of oleic acid (OA) to produce renewable diesel. The La(10)zeo(90) catalyst showed a conversion of OA up to 99 % with 83 % C15 and C17 selectivity after the reaction at 350 ◦C for 2 h under 4 MPa H2 pressure. The superior activity of La(10)zeo(90) was attributed to the synergistic interaction between La-Si-Al, a sufficient amount of weak+ medium acid sites and excellent textural properties (large pore diameter). Larger pore diameter of La(10)zeo(90) is highly desirable as it will generate greater diffusion of bulky molecules, thereby improving the accessibility of the reactant and hence excellent catalytic activity. The vacuum distillation was used to purify the crude liquid product (CLP), producing high-quality diesel fractions mainly comprising C14, C15, and C17 fractions.